HUBUNGAN KEJELASAN DAN KELENGKAPAN PENULISAN DIAGNOSA PENYAKIT BRONCHITIS ACUTE DENGAN KETEPATAN PENGODEAN DIAGNOSA PENYAKIT BERDASARKAN ICD 10 DI BANGSAL RAWAT INAP PENYAKIT DALAM RS MITRA MEDIKA BATANG HARI - Maisharoh Maisharoh; Dian Sari; Dea Rosanti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Coding is one of the medical record data processing activities in providing codes with letters or numbers or a combination of letters and numbers that represent data components. Of the 10 medical record files selected at random, 6 (60%) files were found to be coding inaccuracy, while 4 (40%) files were in accordance with ICD-10. The purpose of this study was to determine the accuracy of the diagnosis code for acute bronchitis in inpatients in the internal medicine ward at Mitra Medika Batanghari Hospital. This type of research uses a descriptive method with a quantitative approach. The population is 95 medical record documents for inpatient acute bronchitis. This research was conducted in July 2021. The sampling technique used a saturated sample. Data analysis used bivariate analysis with SPSS program. The results showed that there were 56 (58.9%) medical records that were not accurate in coding the diagnosis of acute bronchitis for inpatients in the internal medicine ward, 42 (44.2%) medical records for the clarity of writing a diagnosis of acute bronchitis for inpatients in the medical ward. in which it is not clear and 35 (36.8%) medical records completeness of writing a diagnosis of acute bronchitis in inpatients in an internal medicine ward that are incomplete, and the results of bivariate analysis show that there is a relationship between clarity and accuracy of diagnostic coding pvalue = 0.001 (p<0 ,05). and there is a relationship between clarity and completeness with the accuracy of diagnostic coding pvalue = 0.005 (p<0.05)Keywords: Accuracy, Coding, Acute Bronchitis.